Accounting, organizations, and institutions essays in honour of Anthony Hopwood - Hopwood, Anthony G.; Chapman, Christopher S.; Cooper, David (David J.); Miller, Peter, 1954- (Oxford : Oxford University Press, 2009)
This text showcases some of the pioneering work that has persuasively explained to what extent economic life is constituted through the calculative practices of accounting.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Accounting; Accounting -- Social aspects